유아의 애착 및 어머니 - 유아 상호작용과 또래 상호작용간의 관계 - 이영(Young Lee); 나유미(Yu Mee Rah) (Korean Journal of child studies, 1999)
This study analyzed the relation of children's attachment security and mother-child interaction to children's peer interactions. The subjects were 51 preschoolers, 44 to 57 months of age and their mothers. Attachment was assessed using the Attachment Q-set (Waters, 1987), mother-child interactions at home were observed with the use of the Teaching Strategies Rating Scales (Erickson, Sroufe, Egeland, 1985), and peer interactions were observed during free play time, using the Holloway and Erickson(1988) categories. Pearson correlation and multiple regression showed that attachment security scores were negatively related to dependency toward peers. Mother's "structure and limit setting" and "respect for child's autonomy" were positively related to "helping with peers" and negatively to "asking for help" and "physical attack". The variables accounting for dependency toward peers were mother's hostility and attachment security.